Electro-biocatalytic conversion of carbon dioxide to alcohols using gas diffusion electrode. (October 2018) - Srikanth, Sandipam; Singh, Dheer; Vanbroekhoven, K.; Pant, Deepak; Kumar, Manoj; Puri, S.K.; Ramakumar, S.S.V.
Graphical abstract: Highlights: C4-organics produced from carbon dioxide through electro-biocatalysis. Solubility and bio-availability of carbon dioxide increased with gas diffusion electrode. Uncontrolled pH triggered alternate metabolic pathways towards butyric acid and alcohols. 34 g/l of total products were accumulated in 90 days with coulumbic efficiency of 49%. Ethanol and butanol occupied about 45% and 16% of total products, respectively. Abstract: Impact of gas diffusion electrodes (GDEs) was evaluated in enhancing the CO2 bio-availability for its transformation to C4-organics, especially to alcohols using selective mixed culture. Observed current density was more stable (9–11 A/m 2 ) than submerged experiments reported and significantly varied with pH and respective CO2 solubility. Uncontrolled operating pH (starting with 8.0) showed its impact on shifting/triggering alternate metabolic pathways to increase the carbon length (butyric acid) as well as producing more reduced end products, i.e. alcohols. During the experiments, CO2 was transformed initially to a mixture of volatile fatty acids dominated with formic and acetic acids, and upon their accumulation, ethanol and butanol production was triggered. Overall, 21 g/l of alcohols and 13 g/l of organic acids were accumulated in 90 days with a coulombic efficiency (CE) of 49%. Ethanol and butanol occupied respectively about 45% and 16% of total products, indicating larger potential of this technology.